Comparative assessment of the strength and endurance of the respiratory muscles in skiers and wrestlers - Segizbaeva M.O. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to compare the maximal inspiratory strength and endurance of inspiratory muscles in athletes engaged in different types wrestling and skiing. Methods and structure of the study. The maximal inspiratory pressure (MIP) was measured in athletes of wrestlers and skiers, as well as in volunteers without special physical training before and after incremental cycling exercise "to exhaustion". Results and conclusion. The highest values of the maximal inspiratory pressure were found in athletes of skiers (155.4±9.9 cm H2O), whose training is aimed at developing the aerobic capabilities. At the same time, the strength of inspiratory muscles decreased both in the control group of subjects (by 12%), and in athletes-skiers (by 8%) and wrestlers (by 11%) after incremental cycling exercise "to exhaustion", which is probably due to the development of inspiratory muscles fatigue. Specific training of the respiratory muscles can be an effective method for the increase in strength and endurance in both wrestlers and skiers, as well as in healthy physically active people.